Tracing the impact of first-year writing: identity, process, and transfer at a public university - Wilder, Laura, author; Utah State University Press, publisher (Colorado State University. Libraries, 2024)
Presents the results of a large-scale, five-year longitudinal study of college writers that offers important contributions to longitudinal research on college writers in rhetoric and composition related to comparisons of students who did and did not take first year writing.--Provided by publisher.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- United States; Academic writing -- Study and teaching (Higher) -- United States; Education, Higher -- Curricula -- United States